Global hospitality and tourism management technologies - Ordóñez de Pablos, Patricia 1975-; Tennyson, Robert D.; Zhao, Jingyuan 1968- (Business Science Reference, 2012)
"This book is a comprehensive source of information for those interested in tourism and hospitality management, approaches, and trends, and, covers the emerging research topics that will define the future of IT and cultural development in the 21st century" - Provided by publisher
Includes bibliographical references
Keywords: Tourism / Management; Hospitality industry